ANALYSIS OF THE EFFECT OF THE USE OF PRODUCTION FACTORS AND INCOME OF SHALLOT FARMING IN SUMLILI VILLAGE, WEST KUPANG SUB-DISTRICT, KUPANG DISTRICT - Riwu, Viceroy Ruben Junior; Hendrik, Ernantje; Siubelan, Yakobus C.W.; Suek, Johanna (Buletin Ilmiah Impas, 2025)
This study aims to analyze the effect of the use of production factors on shallot production and shallot farming income in Sumlili Village, West Kupang District, Kupang Regency. The sampling technique was done by simple randomization which amounted to 38 respondents. The method used in this research is quantitative, with primary data obtained through direct interviews with respondent farmers and secondary data collected from the Central Bureau of Statistics and related agencies. This study analyzed five variables, namely land area, seeds, fertilizers, pesticides, and labor, using multiple linear regression analysis with Cobb-Douglas production function, as well as classical assumption tests and income analysis. The results showed that three production factors, namely land area, seeds, and fertilizers, had a significant effect on shallot production, while pesticides and labor had no significant effect. Simultaneously, the five variables have a significant influence on shallot production in Sumlili Village with a contribution of 80.7%, while the rest is influenced by other variables not studied. Based on income analysis, the average shallot production per farmer in Sumlili Village is 1,296 kg, with productivity per hectare reaching 5,130 kg and total production of 49,250 kg from 38 respondents, with a selling price in the season of Rp.15,000 per kilogram so that the amount of revenue per farmer is Rp.19,440,789. and the amount of revenue per hectare is Rp.76,953,125 with total production costs per farmer of Rp.6,061,197 and total costs per hectare of Rp.23,992,240 so that the average income per farmer is Rp.13,279,592 while the average income per hectare is Rp.52,960,885.